External Quality Assessment for the Detection of Chlamydia trachomatis in Urine Using Molecular Techniques in Belgium. (25th June 2015) - China, Bernard; Vernelen, Kris
Abstract : Chlamydia trachomatis is a major cause of sexually transmitted bacterial disease worldwide. C. trachomatis is an intracellular bacterium and its growth in vitro requires cell culture facilities. The diagnosis is based on antigen detection and more recently on molecular nucleic acid amplification techniques (NAAT) that are considered fast, sensitive, and specific. In Belgium, External Quality Assessment (EQA) for the detection of C. trachomatis in urine by NAAT was introduced in 2008. From January 2008 to June 2012, nine surveys were organized. Fifty-eight laboratories participated in at least one survey. The EQA panels included positive and negative samples. The overall accuracy was 75.4%, the overall specificity was 97.6%, and the overall sensitivity was 71.4%. Two major issues were observed: the low sensitivity (45.3%) for the detection of low concentration samples and the incapacity of several methods to detect the Swedish variant of C. trachomatis . The reassuring point was that the overall proficiency of the Belgian laboratories tended to improve over time.